Pengaruh Pemberain Air Jahe terhadap Nyeri Menstruasi di Posyandu Remaja Danau Sipin Kota Jambi - Julaecha, Julaecha; Fatmawati, Tina Yuli; Nurita, Suci Rahmani (Jurnal Akademika Baiturrahim Jambi, 2025)
Menstrual pain (dysmenorrhea) is a health problem often experienced by fertile women and can disrupt daily activities. The prevalence of dysmenorrhea in Indonesia is quite high, with 54.98% primary dysmenorrhea and 9.36% secondary dysmenorrhea. The use of natural ingredients such as ginger is a popular alternative because ginger contains high levels of essential oils and the chemical content of gingerol in ginger can block prostaglandins, thereby reducing pain during menstruation. Ginger is also readily available and inexpensive. This study aims to determine the effect of ginger water on dysmenorrhea pain in adolescent girls in the Danausipin sub-district of Jambi City. The research method used was a pre-experimental design with a one-group pre-post test. The sample was 22 adolescent girls who experienced menstrual pain and were willing to be respondents. Menstrual pain was measured before and after ginger water administration using the Numeric Rating Scale (NRS). The results of the study showed that before the intervention, 50% of the pain scale felt was mild and moderate menstrual pain, after the intervention, 22.7% did not experience pain and 63.6% experienced mild pain. There was an effect of giving ginger water on reducing menstrual pain with a P value of 0.000. Ginger water can be used as an alternative natural treatment for menstrual pain